Indonesian behavior of information related to covid-19 - Fajri, Choirul; Nusantari, Krysna Yudy (International Journal of Communication and Society, 2022)
So far, studies related to information behavior, especially in relation to the Covid-19 pandemic, are still rarely carried out. Existing studies tend to only examine the behavior of information related to a hoax news. Therefore, this research will examine the information behavior of the public in relation to how they search, verify, use, and also disseminate information related to the Covid-19 pandemic. Information behavior of the public to obtain correct information is very much needed during the Covid-19 pandemic in the midst of a lot of false/hoax information circulating. This study aims to find out how the information behavior of the Indonesian society during the Covid-19 pandemic. This research was conducted using mixed methods, which were quantitative and qualitative. Quantitative data was obtained by distributing questionnaires online to the public, while qualitative data was obtained by conducting interviews as well as literature study. The results of this study indicate that the information behavior of the Indonesian people is good, it is proven that they always seek information related to Covid-19 intensely, are able to choose the right information, and take an attitude towards false/hoax information received.